Human planting strategies and its relation to climate change during ∼4,800–3,900 BP in the mid-lower Hulu River Valley, northwest China - Wei, Wenyu; Ma, Minmin; Chen, Guoke; Dong, Jiajia; Wu, Zekun; Li, Haiming; Li, Xiaobin (Frontiers in Earth Science, 2023)
The response of agricultural societies to global climate events during the Neolithic (e.g., 4.2 ka event) is a scientific issue of general interest. In the mid-lower Hulu River Valley of northwest China, millet cultivation became the primary subsistence during the late Neolithic. Local paleoclimate studies have detected a notable decline in temperature and precipitation around 4400 BP, while the Qijia culture (4200–3600 BP) sites far outnumber those of the Lower Changshan culture (4800–4400 BP) in the area. Why the intensity of millet farming groups increased when climate was relatively cold and dry, however, has not been well understood. To explore the issue, we performed archaeobotanical analysis, grain size measurement, stable isotope analysis and radiocarbon dating in the excavated sites of the Zhongtianxingfucheng (ZTXFC) and Wangjiayangwan (WJYW), which are dated to between ~4800–4400 BP and ~4200–3900 BP, respectively. Our results demonstrate the overall declines in the proportion, grain sizes and carbon isotope values of millets from the WJYW site compared to ZTXFC. The nitrogen isotopes of millets from the two sites are similar (foxtail millet: 6.8±1.9‰ (ZTXFC), 7.5±1.5‰ (WJYW); broomcorn millet: 7.3±2.0‰ (ZTXFC), 7.5±1.2‰ (WJYW)). These results suggest that the degree of field management during ~4200–3900 BP was lower than ~4800–4400 BP in the mid-lower Hulu River Valley. Instead of improving cultivation management or altering cropping patterns, Qijia millet farmers might have adopted a strategy of expanding cultivated lands to promote the social development under a relatively cold-dry climate.